‘CENSORIA POTESTAS’ OKTAWIANA AUGUSTA - Tarwacka, Anna (Zeszyty Prawnicze, 2016)
OCTAVIAN AUGUSTUS’ ‘CENSORIA POTESTAS’ Summary Octavian completed the census and lustrum three times. His policy was to restore the mores maiorum. When promulgating his lex Iulia de maritandis ordinibus he read censor Metellus’ speech in the senate and published it as an edict. Augustus himself did not mention censoria potestas. From the sources it may be deduced that he and Agrippa got it only during the first census in 29 BC. Later the princeps performed censorial duties vested with an imperium. He wanted to abide to the republican principles as much as possible and that is why he avoided assuming too many magistracies and usually appointed a colleague. That notwithstanding, Augustus was considered censor by his contemporaries.